(untitled) (Journal of Plant Disease Sciences, 2021)
Oyster mushroom is a highly efficient lignin and cellulose degrading fungus and its cultivation is one of the most cost-effective organic recycling processes. A variety of agro-wastes can be used as substrate for its cultivation. Despite the abundance of agro-wastes available every season, little effort has been made to use these agro-wastes for mushroom production. The ease of access to raw materials, the current experiment was carried out with locally available agro-wastes such as paddy straw, maize stove, banana waste, betel nut cover, and their mixture in 1:1 ratio yielding a total 11 different treatments. The paddy straw substrate had the fastest mycelial run (12.66 days), the earliest pin head formation (15.66 days), the highest yield (685) and the highest biological efficiency (102.33%).